2013
DOI: 10.1063/1.4802664
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling conduction in graphene/(poly)vinyl alcohol composite

Abstract: Graphene/(Poly)vinyl alcohol (PVA) composite film with thickness 60µm were synthesized by solidification of a PVA solution comprising of dispersed graphene nanosheets. The close proximity of the graphene sheets enables the fluctuation induced tunneling of electrons to occur from one sheet to another. The dielectric data show that the present system can be simulated to a parallel resistance-capacitor network. The high frequency exponent of the frequency variation of the ac conductivity indicates that the charge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…While the dispersion of nanoparticles does not allow direct mechanical contact between the particles, the electron transport is only possible through the polymer barrier [24][25][26] . In such case, the conduction between the CNTs is influenced by the quantum tunnelling barrier or tunnelling voltage resulting in interparticle tunnelling conduction between adjacent particles 27,28 , or by variable range hopping mechanism [29][30][31] . However, a long range microscopic conduction mechanism of electrons within a composite is governed by the percolation phenomenon 32,33 with the most important element of the theory-percolation threshold, describing the minimum volume content of the conductive nanoparticle providing the electrical conductivity 34 .…”
mentioning
confidence: 99%
“…While the dispersion of nanoparticles does not allow direct mechanical contact between the particles, the electron transport is only possible through the polymer barrier [24][25][26] . In such case, the conduction between the CNTs is influenced by the quantum tunnelling barrier or tunnelling voltage resulting in interparticle tunnelling conduction between adjacent particles 27,28 , or by variable range hopping mechanism [29][30][31] . However, a long range microscopic conduction mechanism of electrons within a composite is governed by the percolation phenomenon 32,33 with the most important element of the theory-percolation threshold, describing the minimum volume content of the conductive nanoparticle providing the electrical conductivity 34 .…”
mentioning
confidence: 99%
“…This is much more apparent in s, which can have monotonic increase, decrease or a local maximum vs. T. S can be affected primarily in terms of its magnitude and the characteristics of its maximum value (Fig. 8,[16][17][18][19][20][21] For example, the barrier heights are found in the 1-1000 meV range, the overlap areas are in the 0.1-100 nm 2 intervals, while w is found to be in the nm scale. The thermal conductivity typically increases nonlinearly as a function of T (Fig.…”
Section: Properties Of the Fluctuation-induced Tunnelingmentioning
confidence: 98%
“…Studies have shown that although such polymers are conducting, their transport is different than that of inorganic compounds. 14,[16][17][18][19][20][21] Much of the existing work on heavily-doped polymers is interpreted in terms of this expression for s. The Seebeck coefficient is also fit with adjustable parameters from experiment. Doping these materials introduces carriers that become trapped in these chains and form polarons and bi-polarons, 3,13 which represent coupling between charge and distortion in the chain.…”
Section: Introductionmentioning
confidence: 99%
“…A PVA solution with a concentration of 10% w/v was prepared by dissolving PVA in deionized water at 90 C under stirring for 2 h. To prepare PVA/CB composite, 10 mL of PVA solution was mixed with the appropriate amount of CB (20,30,40,50, and 60%wt). Then 2.8 mL of crosslinking solution, prepared from 50%w/v methanol (the quencher), 10%w/v acetic acid (the pH controller), 1.20%w/v glutaraldehyde, and 10%w/v sulfuric acid (the catalyst), with solution volume ratio of 3 : 2 : 1 : 1, was added into the mixture under constant stirring for 15 min, in order to obtain a uniform distribution of the filler.…”
Section: Preparation Of Composite Filmsmentioning
confidence: 99%
“…In comparison with PVA/ CB composites, the loading for such the onset of transition was lower. 40,41 Many companies have developed ESD control films those commercially available (Table III). As seen from SEM micrographs [ Figure 1(h,i)], Al particles displayed angular morphology with low to medium sphericity.…”
Section: Electrical Conductivitymentioning
confidence: 99%